2015
DOI: 10.1038/cr.2015.9
|View full text |Cite
|
Sign up to set email alerts
|

Cationic nanocarriers induce cell necrosis through impairment of Na+/K+-ATPase and cause subsequent inflammatory response

Abstract: Nanocarriers with positive surface charges are known for their toxicity which has limited their clinical applications. The mechanism underlying their toxicity, such as the induction of inflammatory response, remains largely unknown. In the present study we found that injection of cationic nanocarriers, including cationic liposomes, PEI, and chitosan, led to the rapid appearance of necrotic cells. Cell necrosis induced by cationic nanocarriers is dependent on their positive surface charges, but does not require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
195
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(203 citation statements)
references
References 54 publications
6
195
1
1
Order By: Relevance
“…Moreover, when examining the inhibition of malignant ascites, the F-PLP/pIL15 group was found to have a smaller ascites volume than the other three lipoplex groups (PLP/pc3.1, F-PLP/pc3.1 and PLP/pIL15; data not shown). Furthermore, the two vector treatment groups, PLP/pc3.1 and F-PLP/pc3.1, generated a weak antitumor effect compared to the NS group (Figure 2a – 2c), which may be due to nonspecific cytotoxicity in liposomes or lipoplexes containing DOTAP [40]. …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, when examining the inhibition of malignant ascites, the F-PLP/pIL15 group was found to have a smaller ascites volume than the other three lipoplex groups (PLP/pc3.1, F-PLP/pc3.1 and PLP/pIL15; data not shown). Furthermore, the two vector treatment groups, PLP/pc3.1 and F-PLP/pc3.1, generated a weak antitumor effect compared to the NS group (Figure 2a – 2c), which may be due to nonspecific cytotoxicity in liposomes or lipoplexes containing DOTAP [40]. …”
Section: Resultsmentioning
confidence: 99%
“…Among alternative nonviral intraperitoneal gene transfection systems, methods based on cationic liposomes and polymers are cytotoxic and the cationic charge induces an inflammatory response (Wei et al, 2015). We have previously reported that calcium carbonate microflowers can achieve effective and safe intraperitoneal gene transfection (Fumoto et al, 2012), but the transgene-positive tissues or cells in the peritoneal cavity cannot be controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Cationic liposomes might induce apoptosis, often after 24-48 h exposure, 9,12,48,49 but they can also trigger acute cell necrosis, even before the occurrence of apoptosis, in a positive surface charge-dependent manner. Cationic liposomes might induce apoptosis, often after 24-48 h exposure, 9,12,48,49 but they can also trigger acute cell necrosis, even before the occurrence of apoptosis, in a positive surface charge-dependent manner.…”
Section: Paper Toxicology Researchmentioning
confidence: 99%